Metabolomic and lipidomic insights into the impact of Euglena gracilis-derived β-glucan supplementation on sow colostrum and milk composition - Jakavat Ruampatana; Takele Feyera; Unchean Yamsrikaew; Methaporn Juarjan; Kunaporn Homyog; Wanwimon Mekboonsonglarp; Sarn Settachaimongkon; Morakot Nuntapaitoon (Computational and Structural Biotechnology Journal)
Euglena gracilis, an algae-derived source of β-glucan, exhibits prebiotic activity that enhances colostrum quality and improves growth, though the underlying mechanisms remain unclear. This study investigates the effects of E. gracilis supplementation during late gestation and lactation on sow colostrum and milk biomolecular profiles. Sixty-one crossbred sows (Landrace × Yorkshire) were assigned to a standard diet (CON; n = 30) or the CON diet supplemented with 1 g/sow/day of E. gracilis (TRT; n = 31) from day 85 of gestation until day 21 of lactation. Sow performance, including litter size and weight, was recorded from birth to day 21 of age. Colostrum samples (n = 20; 10 sows/group) were collected within 1 h of farrowing, and milk samples were collected from the same sows on days 3 and 10 of lactation to assess alterations in non-volatile polar metabolites (NVM), fatty acids (FA), and associated metabolic pathways. On average, the litter size at birth was 14.2 ± 2.5 piglets/litter, with no effect of dietary treatment from birth to day 21 of lactation (P > 0.05). However, piglets suckled by TRT sows tended to have higher average daily gain from birth to day 21 of age than those suckled CON sows (191.0 ± 6.7 vs. 173.6 ± 6.8 g/day, P = 0.073). Chemometric analysis revealed distinct NVM and FA profiles between the groups, particularly in the colostrum. Although E. gracilis supplementation influenced the contents of multiple metabolites, focus has been given to those that have direct impact on piglet development, including increased colostrum leucine (P = 0.001), threonine (P < 0.001), and N-acetylglucosamine (P = 0.002), enhancing colostrum quality and immunomodulatory potential. Elevated colostrum gamma-linolenic acid (P = 0.047) and arachidonic acid (P = 0.019) levels suggested enhanced immune development. Pathways associated with amino sugars and nucleotide sugars and glucose-related metabolism in colostrum were also modulated. These findings suggest E. gracilis-derived β-glucan as a potential dietary supplement for enhancing sow colostrum quality and piglet growth.